Alternative Functions of Cell Cycle-Related and DNA Repair Proteins in Post-mitotic Neurons - Akagawa, Remi; Nabeshima, Yo-ichi; Kawauchi, Takeshi (Frontiers in Cell and Developmental Biology, 2021)
Proper regulation of neuronal morphological changes is essential for neuronal migration, maturation, synapse formation and high-order function. Many cytoplasmic proteins involved in the regulation of neuronal microtubules and the actin cytoskeleton have been identified. In addition, some nuclear proteins have alternative functions in neurons. While cell cycle-related proteins basically control progression of the cell cycle in the nucleus, some of them have an extra-cell cycle-regulatory function (EXCERF), such as regulating cytoskeletal organization, after exit from the cell cycle. Our expression analyses showed that not only cell cycle regulators, including cyclin A1, cyclin D2, Cdk4/6, p21cip1, p27kip1, Ink4 family and RAD21, but also DNA repair proteins, including BRCA2, p53, ATM, ATR, RAD17, MRE11, RAD9 and Hus1, were expressed after neurogenesis, suggesting that these proteins have alternative functions in post-mitotic neurons. In this perspective paper, we discuss the alternative functions of the nuclear proteins in neuronal development, focusing on possible cytoplasmic roles.